2015
DOI: 10.1371/journal.pone.0143324
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Mannoheptulose Does Not Significantly Alter Daily Energy Expenditure in Adult Labrador Retrievers

Abstract: Mannoheptulose (MH), a sugar found in avocados that inhibits glycolysis in vitro, has been preliminarily investigated as a novel food ingredient for dogs. This study aimed to determine the effects of dietary MH, delivered as an extract of un-ripened avocado, on energy expenditure (EE) in healthy adult Labrador Retriever dogs (total of 12 dogs, 26.99 ± 0.634 kg, 4.9 ± 0.2 y). The study was a double-blind, cross-over with each dog receiving both dietary treatments, control (CON) and MH (400 mg/kg of diet; 6 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…McKnight et al 32 also found no significant effects of an AvX diet delivering 6 mg/kg for 9 weeks on plasma glucose kinetics in Labrador Retrievers but did observe significantly reduced postprandial RQ. It is unclear why the differences between these past reports and the findings reported herein occurred regarding the effects of AvX on glucose and insulin levels.…”
Section: ■ Discussionmentioning
confidence: 94%
“…McKnight et al 32 also found no significant effects of an AvX diet delivering 6 mg/kg for 9 weeks on plasma glucose kinetics in Labrador Retrievers but did observe significantly reduced postprandial RQ. It is unclear why the differences between these past reports and the findings reported herein occurred regarding the effects of AvX on glucose and insulin levels.…”
Section: ■ Discussionmentioning
confidence: 94%
“…In Labrador Retrievers fed an AvX diet delivering 2 mg/kg of MH for 22 days, McKnight et al [ 46 ] observed significantly increased fasting RQ and glucose oxidation measured by calorimetry. In another study of Labrador Retrievers eating an AvX diet delivering 6 mg/kg of MH for 9 weeks, McKnight et al [ 47 ] also observed significantly reduced post-prandial RQ. It is uncertain why differences between these past studies in dogs and cats and the current findings in mice occurred regarding the effects of AvX on glucose and insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies applying a similar formulation of MH-enriched AvX in studies of dogs and cats have produced results that are incongruent with those of our mouse study. Ranging from 14 to 42 days of treatment delivering MH doses from 2 to 8 mg/kg, investigations of Labrador Retrievers, Beagles, and domestic cats found no significant effects on circulating levels of glucose or insulin nor on body weight [ 43 , 44 , 45 , 46 , 47 ]. Several significant physiological effects of feeding AvX were observed, however.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol , which is discussed later in the review in more detail, also shows anti-glycolytic activities, as it shows inhibitory effects on hexokinase in cell lines ( 97 ). Apart from these phenolic, plant-based compounds, mannoheptulose , a rare sugar, also inhibits hexokinases and was suggested as a CRM which is prominently present in unripe avocados ( 98 ), but has produced mixed results in preclinical work ( 17 ).…”
Section: Glycolysis Inhibitorsmentioning
confidence: 99%